1995
DOI: 10.1111/j.1570-7458.1995.tb01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization and sex allocation in response to host size in two ectoparasitoid wasps on subcortical beetles

Abstract: Patterns of host resource utilization and sex ratio manipulation in relation to host size were investigated for two solitary ectoparasitoid wasps, Atanycolus initiator and Spathius brevicaudis (Hymenoptera Braconidae). Both species parasitize subcortical beetles on the trunks of Japanese pine trees. A. initiator is on average 8 times larger in body weight and has an ovipositor that is 3.7 times longer than that of S. brevicaudis. In both parasitoids, the size of emerging wasps was positively correlated with ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Host size, however, may not be a suitable proxy of host quality for idiobiont parasitoids under two conditions. Available resources will be overestimated if the parasitoid larva does not completely consume all host tissues, because they are in surplus to parasitoid requirements (Urano and Hijii 1995) or cannot be digested. More important perhaps, shape parameters are likely to confound estimates of the amount of available host resources derived from length measurements and, possibly, lead to erroneous conclusions about qualitative dierences between hosts.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Host size, however, may not be a suitable proxy of host quality for idiobiont parasitoids under two conditions. Available resources will be overestimated if the parasitoid larva does not completely consume all host tissues, because they are in surplus to parasitoid requirements (Urano and Hijii 1995) or cannot be digested. More important perhaps, shape parameters are likely to confound estimates of the amount of available host resources derived from length measurements and, possibly, lead to erroneous conclusions about qualitative dierences between hosts.…”
Section: Discussionmentioning
confidence: 98%
“…7). Urano and Hijii (1995) reported that larvae of Spathius brevicaudis and Atanycolus initiator, two braconid ectoparasitoids of various beetles, did not consume all resources if host larvae were relatively large, as opposed to small. The quantity of host remains increased as a percentage of host size in a parasitoid sexspeci®c manner, with the smaller males generally consuming less of the host larva than did the larger females, especially in S. brevicaudis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations